Diagnostic Value of Urinary Microalbumin Level in Postpartum Acute Kidney Injury - Jian ZHANG; Ning LI; Wenling GUO; Chuanyan MA; Guangcheng ZHAO (Iranian Journal of Public Health, 2018)
Background: We aimed to explore the diagnostic value of urinary microalbumin (mALB) level in postpartum acute kidney injury.